Linearized thermal model for power transformer's hourly top-oil temperature estimation - Pare, Meden C.; Orillaza, Jordan Rel (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
The loss-of-life of the transformers insulation depends mainly on the hottest-spot temperature where the top-oil temperature is a key factor. Available top-oil thermal models in the literature are subjective to the transformers characteristics (size, weight, type of cooling, etc.) and require data that are neither usually available nor monitored by the utilities. This thesis presents a top-oil thermal model using variables that are available and monitored by the utilities. Specifically, a linearized model of the top-oil temperature as a function of transformer loading, ambient temperature and sunshine duration is presented. The proposed model was analyzed and simulated on a 25 MVA transformer from April 2014 to September 2014 and some days of October 2015 with a minimal difference of 2-3 degree celsius between the actual and calculated results. It was also found out that the proposed model cal still reasonably estimate top-oil temperature even on a 10 MVA transformer. Agreements between the calculated and actual top-oil temperature show that the model can convincingly estimate the thermal behavior of a transformer. Agreements between the calculated and actual top-oil temperature show that the model can convincingly estimate the thermal behavior of a transformer between 10MVA - 25MVA. The effect of sunshine duration on the loss-of-life, hottest-spot and top-oil temperature of the transformer was investigated. It was found out that as high as 14 percent difference on the loss-of-life on a daily load basis could have taken if sunshine duration is controlled by installing a shed.
Thesis (M.S. Electrical Engineering)--University of the Philippines Diliman
Keywords: Electric transformers; Electric insulators and insulation -- Oils